Makna Teologis Memberi Persembahan Perpuluhan Dalam Perjanjian Lama (International Forum of Researchers and Lecturers, 2023)
There is no denying that it is one measure of the Christian's relationship with God. Personal finances, especially in terms of giving and keeping a tithe tax offering. Tithing is an important issue in Christian finance. Some believe that this is a tax to God for a happy life. Despite life's difficulties. Some people do not pay tithing. unmanageable income. In fact, there are things that we cannot give. Because he enjoys spending too much money on his life. Also, some Christians tithe eagerly, but for no apparent reason. Because that's what the church and family taught me since I was little.